Mislocalization of Nucleocytoplasmic Transport Proteins in Human Huntington’s Disease PSC-Derived Striatal Neurons - Lange, Jenny; Wood-Kaczmar, Alison; Ali, Aneesa; Farag, Sahar; Ghosh, Rhia; Parker, Jennifer; Casey, Caroline; Uno, Yumiko; Kunugi, Akiyoshi; Ferretti, Patrizia; Andre, Ralph; Tabrizi, Sarah J. (Frontiers in Cellular Neuroscience, 2021)
Huntington’s disease (HD) is an inherited neurodegenerative disorder caused by a CAG repeat expansion in the huntingtin gene (HTT). Disease progression is characterised by the loss of vulnerable neuronal populations within the striatum. A consistent phenotype across HD models is disruption of nucleocytoplasmic transport and nuclear pore complex (NPC) function. Here we demonstrate that high content imaging is a suitable method for detecting mislocalisation of lamin-B1, RAN and RANGAP1 in striatal neuronal cultures thus allowing a robust, unbiased, highly powered approach to assay nuclear pore deficits. Furthermore, nuclear pore deficits extended to the selectively vulnerable DARPP32+ subpopulation neurons, but not to astrocytes. Striatal neuron cultures are further affected by changes in gene and protein expression of RAN, RANGAP1 and lamin-B1. Lowering total HTT using HTT-targeted anti-sense oligonucleotides partially restored gene expression, as well as subtly reducing mislocalisation of proteins involved in nucleocytoplasmic transport. This suggests that mislocalisation of RAN, RANGAP1 and lamin-B1 cannot be normalized by simply reducing expression of CAG-expanded HTT in the absence of healthy HTT protein.